2006
DOI: 10.1007/s00192-006-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women with stress urinary incontinence

Abstract: The objective of this study was to identify clinical and demographic factors associated with incontinence-related quality of life (QoL) in 655 women with stress urinary incontinence who elected surgical treatment. The following factors were examined for their association with QoL as measured with the Incontinence Impact Questionnaire (IIQ): number of incontinence (UI) episodes/day; self-reported type of UI symptoms (stress and urge); sexual function as measured by the Prolapse/Urinary Incontinence Sexual Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 22 publications
5
41
1
8
Order By: Relevance
“…Some studies found that mixed and urgency UI vs stress UI had a significantly higher impact on quality of life [4,[11][12][13]. Conversely, others reported that stress versus urgency UI had a more profound effect on quality of life [14]. However, most previous studies had a smaller Fig.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Some studies found that mixed and urgency UI vs stress UI had a significantly higher impact on quality of life [4,[11][12][13]. Conversely, others reported that stress versus urgency UI had a more profound effect on quality of life [14]. However, most previous studies had a smaller Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Previous cross-sectional studies have reported differences in symptom severity, quality of life, and bother by UI subtype [4,[11][12][13][14][15][21][22][23][24][25]. Some studies found that mixed and urgency UI vs stress UI had a significantly higher impact on quality of life [4,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary incontinence is a common problem resulting in decreased quality of life in middle-aged women [1,2]. A major factor contributing to urinary incontinence is damage to the pelvic floor by the weight of the fetus during pregnancy and passage of the fetus during vaginal delivery through the pelvic cavity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is associated with significant impairment in the quality of life of women [2]. The number of SUI surgical procedures has increased substantially over the last two decades, with increases in both outpatient and inpatient procedures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%